Estado nutricional asociado a los hábitos alimentarios en la escuela Jeniffer y Jaely Ludeña del Cantón Calvas Provincia de Loja 2021 - Cueva Romero, Jefferson José (2022)
Eating habits have a direct influence on the growth, development and quality of life of schoolchildren, so that poor or excessive eating leads to malnutrition; it is important to educate the community in general about eating habits. Therefore, the objective was to determine the relationship between the nutritional status and eating habits of the students of basic education of the school Jeniffer y Jaely Ludeña Jiménez of the Calvas Province of Loja 2021. The present work was based on a descriptive, quantitative, correlative and cross-sectional study in which the total population of 60 schoolchildren aged 6 to 9 participated. Information was collected through weight and height control to determine the BMI, which was analyzed using the MSP growth curves, and a survey on eating habits was also applied to the participants' representatives. The results showed that: 75% of schoolchildren have a normal nutritional status, 18% risk of overweight and 7% overweight. Regarding eating habits, it was determined that 65% have healthy habits, 10% very healthy and 25% unhealthy habits. In relation to the study variables, it is confirmed that there is a high negative correlation with a coefficient of, -88 by means of the non-parametric correlation of Rho Spearman, with a P value less than 0.05 the null hypothesis is rejected and the alternating hypothesis is accepted. School children predominate the normal nutritional status with healthy eating habits, which indicates that the nutritional status will be reflected according to the diet and types of habits maintained by the school